MORPHOLOGICAL STRUCTURE OF INTESTINAL LAMBALISM, SYMPTOMS OF LAMBLIOSIS, DIAGNOSIS AND TREATMENT METHODS (Proceedings of International Educators Conference, 2024)
Occurs in the form of vegetative as well as cysts in the cycle of life. The vegetative form is non-existent, 12-15km long and 8-10km wide. On the front side of the body is a disc that serves to attach to the intestinal epithelium. In the middle of the body are two base threads — axostils. Using axostils, the body of the parasite is divided into two wire metric nymphs, each with one nucleus. At the front of the axostils are several blepharoplasts, which provide energy to 3 pairs of chives. The fourth pair of chicks lies on the back of the axostils. The parasite does not have digestive organs, it is fed by an osmotic path. The method of reproduction is non-sexual, the path of division into vows is accomplished by mitosis. The cysts of the lambs are oval in shape and range in length from 10-14 μm. The two-story shell is clearly visible. Immature cysts have 2 nuclei and 4 nuclei when mature. The development cycle of lamblia is simple, and the period of life consists of the exchange of vegetative and cystic forms of the parasite. Vegetative forms live and multiply in a person’s duodenum. In animals infected by experimental (experimental) pathways, lamblids are found in the upper parts of the small intestine. Some of them are wrapped in cysts, released into the external environment, and remain a source of human transmission of lambliosis. The source of lamblioz infection is the patient and the parasite carriers. Symptoms of the disease are similar to those of other intestinal diseases. Therefore, the main indicator of diagnosing lyambliosis should be the detection of parasites. But it’s a much harder job. Twelve-fingered intestinal fluid contains vegetative forms of the parasite. The patient is diagnosed with parasitic cysts by iodine staining of the litter.With their rubbish, lambed cysts go out into the external environment and can survive for weeks. To a healthy person, the parasite transmitted by cysts through contaminated food, drinking water, or dirty hands. After the cysts enter the digestive tract, the twelve fingers become a vegetative form in the intestine.